2018
DOI: 10.18521/ktd.382958
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Prevalence of Child Abuse: Use of ICAST-Retrospective Instrument with the First Year Medical Students in a University

Abstract: This study determined the prevalence of child abuse in first year medical students in a Turkish university using the ICAST-R, as well as the relationships between sociodemographic data and abuse. Methods: First-year medical students in a Turkish university have been surveyed between 15th-30th June 2012, using ISPCAN Child Abuse Screening Tool-Retrospective Version (ICAST-R) and a questionnaire to collect sociodemographic data. Data analysis was performed with SPSS 15.0. Results: This study was included 192 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…When the relationship between sexual abuse score and income was evaluated, the scores of students in Eskişehir who evaluated their family's income as low were reported to be higher than those who evaluated their income as normal and high 26 . In a study conducted with medical faculty students, in Mersin and in our study, no relationship was found between family income level and sexual abuse scores 18,31 .…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…When the relationship between sexual abuse score and income was evaluated, the scores of students in Eskişehir who evaluated their family's income as low were reported to be higher than those who evaluated their income as normal and high 26 . In a study conducted with medical faculty students, in Mersin and in our study, no relationship was found between family income level and sexual abuse scores 18,31 .…”
Section: Discussioncontrasting
confidence: 67%
“…In studies conducted in China, Istanbul and Sivas, sexual abuse scores were higher for male students 17,20,21 . In a study conducted with medical faculty students, it was reported that the frequency of childhood sexual abuse was higher in males 31 . In studies conducted with university students in Canada, Istanbul and Hatay, sexual abuse scale scores were reported to be higher in women 19,22,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on 192 students in the first year of medical school at a Turkish university, 56.8% of females and 43.2% of males were assessed using ICAST-R. Physical abuse was reported by 14.6% of participants, emotional abuse by 32.3 %, and sexual abuse by 8.9% [ 11 ]. Another study included 6682 students from 18 schools in Kerala, India, who were surveyed using ICAST-CH to estimate the prevalence of child abuse [ 12 ].…”
Section: Introductionmentioning
confidence: 99%